Influence of the isovalent substitution of la atoms in BaLa4Ti4O15 on the constitution of its slab perovskite-like structure - Titov, Y.A.; Belyavina, N.M.; Slobodyanik, M.S.; Timoschenko, M.V.; Chumak, V.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
Conditions of the substitution of La for Nd atoms in slab perovskite-like structure (SPS) of the titanate BaLa4Ti4O15 are determined. SPS of phase BaLa2,5Nd1,5Ti4O15 with a degree of replacement close to maximal has been determined by X-ray powder diffraction. The analysis of the constitution of SPS BaLa2.5Nd1.5Ti4O15 has shown that the insertion of Nd atoms in SPS BaLa4Ti4O15 results in an increase of the degree of deformation of interblock polyhedra (Va,Ln)1O12 and in a decrease of the length of interblock distances (Va,Ln)1 — 3O1. Both factors destabilize SPS and limit the existence domain of solid solutions of BaLa4–xNdxTi4O15 by the value x ≤ 1.55.